ROLE AND IMPORTANCE OF DESTINATION MANAGEMENT COMPANIES IN DEVELOPING CROATIAN TOURIST DESTINATIONS - Batinic, Ivica (Journal of process management and new technologies, 2018)
Specific wishes, needs and demands of modern consumers/tourists, various infrastructural problems and the lack of effective tourist strategies in most Croatian tourist destinations create the need for an effective destination management which will define and come up with effective destination policy for development and improvement of tourism and connect public and private sectors at the destination. Destination management companies which have a highly professional team of tourist experts and managers can influence the tourist industry development at Croatian tourist destinations. Restructuring receptive tourist agencies into destination companies or establishing destination management companies can affect increasing the pleasure of tourists and excursionists, as well as the development of the tourist product of the destination.